Electronic structures and optical characteristics of fluorescent pyrazinoquinoxaline assemblies and Au interfaces - Soyeong Kwon (Nature Portfolio, 2021)
Abstract Understanding the excitonic processes at the interfaces of fluorescent π-conjugated molecules and metal electrodes is important for both fundamental studies and emerging applications. Adsorption configurations of molecules on metal surfaces significantly affect the physical characteristics of junctions as well as molecules. Here, the electronic structures and optical properties of molecular assemblies/Au interfaces were investigated using scanning probe and photoluminescence microscopy techniques. Scanning tunneling microscopy images and tunneling conductance spectra suggested that the self-assembled molecules were physisorbed on the Au surface. Visible-range photoluminescence studies showed that Au thin films modified the emission spectra and reduced the lifetime of excitons. Surface potential maps, obtained by Kelvin probe force microscopy, could visualize electron transfer from the molecules to Au under illumination, which could explain the decreased lifetime of excitons at the molecule/Au interface.